(untitled) (Journal of Hama University, 2021)
This In-vitro study was conducted to assess the marginal sealing provided by Self-Adhesive resin cement compared to the traditional Total-Etch cement on Porcelain laminate veneers, by studying Microleakage. 24 intact human upper premolars extracted without caries and restorations. they were stored in physiologic saline solution. An Incisal Overlapp preparation was made on enamel surface to receive 24 Porcelain laminate veneers (PLV). The lithium disilicate PLV were fabricated by burnout/ heat pressing of wax pattern with a thickness of 0.5 mm. Sample was divided into two groups of twelve teeth each according to the bonding techniques. Group1: Total-Etch, light cure resin cement (Variolink Esthetic LC, Ivoclar Vivadent) was used. Group2: Self-Adhesive resin cement (SA cement plus, Panavia, Kuraray Noritake) was used without any pre-conditioning of the tooth surfaces of the teeth. The sample was immersed in 0.5% methylene blue dye, temperature of 37C for 12 hours. Each tooth was sectioned Longitudinally and horizontally and evaluated using a stereomicroscope (1500 stereo microscope Nikon Stereo Microscopes-SMZ). The values of dye penetration were recorded. values were documented and statistically analyzed by Mann-Whitney U-test . There were significant differences in the values of microleakage between the two groups. Study concluded that the use of Total Etch technique reduced the microleakage around PLV .